Study of correlation between dietary habits and anemia among adolescent girls in Ranchi and its surronding area - Chaturvedi, Deepak; Chaudhuri, Partha Kumar; Priyanka, .; Chaudhary, Anil Kumar (International Journal of Contemporary Pediatrics, 2017)
Background: It is astonishing to know that 30% of world population suffers from IDA out of which 80 to 90% is in developing countries. In India, 80% of children at 1 to 2 years of age, adolescents, pregnant women and lactating mothers suffer from Iron deficiency. Nutritional anemia is a worldwide problem with prevalence in developing countries (36%) compared to industrialized (8%). Most of the problems are related to dietary habits from initial age of a child. Girls are more at risk because of menstrual Issues and early age marriage. Methods: The present study was conducted on 300 adolescent girls (10-19 years) by asking their last 24 hours’ dietary habits. Results: Among 300 girls 39% were vegetarians and remaining 61% were non-vegetarians. Maximum girls (78%) were in the frequent habit of consumption of junk foods. Mild anemia (34%) was found to be more common than other forms of anemia. Severity of anaemia was found to be gradually increased from early to late adolescent group. Conclusions: Anaemia noted in 82% despite majority (91.7%) of girls having normal BMI. Anemia was more common in vegetarians than non-vegetarians and among vegetarians more common with predominantly rice based diet (‘r’=0.871). There was increased association on consumption of tea and coffee post meals (r=0.892).